Pengaruh Kondisi Keuangan Size Company Dan Opini Audit Tahun Sebelumnya Terhadap Penerimaan Opini Audit Going Concern - Sabrina, Windy; Mustofa, Nur Huri (Al-bank: Journal of Islamic Banking and Finance, 2024)
This study aims to examine the effect of financial condition, company size, and audit opinion of the previous year on the acceptance of going concern opinions. The sample used in this study is companies registered in JII for the 2018-2022 period. Sampling using purposive sampling techniques and obtained 29 companies with an observation period of 5 years so that the total sample is 145 data. The results showed that the financial condition, company size, and audit opinion of the previous year simultaneously affect the acceptance of the going concern audit opinion. The financial condition and audit opinion of the previous year have a partial effect on the receipt of the going concern audit opinion. While the size of the company does not have a significant effect on the acceptance of going concern audit opinions